(untitled) (Constructionism Conference Proceedings, 2025)
As data has become an increasing part of our lives, data science education has sought to support youth in becoming critical consumers of data and authors of data-based claims. Relatively abstract sensor data can pose challenges for young people’s sense-making. We share youth work from a week-long, museum-based data science camp to illustrate the ways youth used portable, low-cost environmental sensors to situate explorations of sensor data in hyper-local contexts in their homes and communities. We also share challenges that some youth faced in translating their locally grounded curiosities into questions appropriate for sensor data research. Even as topics and technologies evolve, we position our findings as underscoring the continued relevance of constructionism’s commitment to personally meaningful projects that authentically reflect learners’ interests.